2017
DOI: 10.1021/acs.joc.7b01851
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Paal–Knorr Intermediates in the Trofimov Synthesis of Pyrroles: Experimental and Theoretical Studies

Abstract: We have used isoxazolo[3,4-b]pyridin-3(1H)-one and isoxazolo[3,4-b]quinolin-3(1H)-one as "masked" heterocyclic hydroxylamines to generate Paal-Knorr intermediates of the Trofimov pyrrole synthesis. The previously inaccessible intermediates, trapped by ethyl propiolate, were obtained by reacting corresponding isoxazolones with 4-fold excess of ethyl propiolate under basic conditions at ambient temperature, and characterized by means of IR and NMR spectroscopic data as well as by single crystal X-ray analysis. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The synthesis of pyrroles from ketoximes and acetylene (Trofimov reaction) is considered as a domino reaction starting from the formation of O ‐vinylketoximes B , which undergo 3,3‐sigmatropic shift to iminoaldehydes D further cyclizing to 5‐hydroxypyrrolines E and giving final products G after a water molecule elimination (Scheme ). This mechanism has been repeatedly confirmed by observation and isolation of main intermediates ( O ‐vinylketoximes B , N , O ‐dialkenylhydroxylamines C and iminoaldehydes D ,), but rarely studied computationally …”
Section: Introductionmentioning
confidence: 79%
“…The synthesis of pyrroles from ketoximes and acetylene (Trofimov reaction) is considered as a domino reaction starting from the formation of O ‐vinylketoximes B , which undergo 3,3‐sigmatropic shift to iminoaldehydes D further cyclizing to 5‐hydroxypyrrolines E and giving final products G after a water molecule elimination (Scheme ). This mechanism has been repeatedly confirmed by observation and isolation of main intermediates ( O ‐vinylketoximes B , N , O ‐dialkenylhydroxylamines C and iminoaldehydes D ,), but rarely studied computationally …”
Section: Introductionmentioning
confidence: 79%
“…Using the B3LYP/6-31G* approach, Saczewski and coauthors studied the [3,3]-sigmatropic shift in N,O-divinyl hydroxylamine (Scheme 4, III → IV in Scheme 1) as well as possible rearrangements of the Paal−Knorr intermediate (iminoaldehyde) in enaminoaldehyde and enaminoenol, obtained during the sigmatropic shift. 22 It was demonstrated that 5-hydroxypyrroline (IV) can be vinylated by acetylene yielding 5-vinyloxypyrroline (Scheme 5), which can further eliminate acetaldehyde. 23 Hence, 5hydroxypyrrolines are intermediates along the reaction path leading to 3H-pyrroles (V → VI in Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Finally, we found that compounds 1 and 2 react with α,β-acetylenic carbonyl compounds (Michael acceptors) to give N-vinyl isoxazolones, which transform into N-vinylhydroxylamines by means of B AC 2 cleavage of C-O bond. The later react with an excess of Michael acceptors to yield N,O-divinylhydroxylamines (enamines) that undergo [3,3]-sigmatropic rearrangement to give Paal-Knorr intermediates (Scheme 1) [39]. These findings prompted us to examine the aza-Michael addition reaction of isoxazolone 2 to double activated electron-deficient acetylene, i.e., dimethyl acetylenedicarboxylate (DMAD).…”
Section: Introductionmentioning
confidence: 99%